Impact of lenvatinib-induced proteinuria and renal dysfunction in patients with thyroid cancer - Shibutani, Yuma; Suzuki, Shinya; Sagara, Atsunobu; Enokida, Tomohiro; Okano, Susumu; Fujisawa, Takao; Sato, Fumiaki; Yumoto, Tetsuro; Sano, Motohiko; Kawasaki, Toshikatsu; Tahara, Makoto (Frontiers in Oncology, 2023)
Background: Proteinuria is the most frequent adverse event of lenvatinib use. However, the association between lenvatinib-induced proteinuria and renal dysfunction remains unclear. Methods: We retrospectively reviewed medical records of patients with thyroid cancer without proteinuria treated with lenvatinib as a first-line systemic therapy at the initiation of treatment to assess the association between lenvatinib-induced proteinuria and renal function and the risk factors for the development of ≥3+ proteinuria on a dipstick test. Proteinuria was assessed by the dipstick test throughout the treatment in all cases. Results: Of the 76 patients, 39 developed ≤2+ proteinuria (low proteinuria group) and 37 developed ≥3+ proteinuria (high proteinuria group). There was no significant difference in estimated glomerular filtration rate (eGFR) between high and low proteinuria groups at each time point, but there was a trend toward a significant decrease in eGFR of -9.3 ml/min/1.73 m2 in all patients after 2 years of treatment. The percentage of change in eGFR (ΔeGFR) significantly decreased in the high proteinuria group compared to that in the low proteinuria group (ΔeGFR: -6.8% vs. -17.2%, p=0.04). However, there was no significant difference in development of severe renal dysfunction with eGFR <30 ml/min/1.73 m2 between the two groups. Moreover, no patients permanently discontinued treatment because of renal dysfunction in both groups. Furthermore, renal function after completion of lenvatinib was reversible. Conclusions: There was no association between the degree of lenvatinib-induced proteinuria and renal function. Therefore, treatment should be continued with attention to renal function, regardless of the degree of proteinuria.